DIALOG SEBAGAI METODE PEMBELAJARAN: STUDI KITAB AL-TARBIYYAH BI AL-HIWAR KARYA ABDURRAHMAN AN-NAHLAWI - Muharir Alwan; Himayatul Izzati (Universitas Islam Negeri Mataram, 2023)
Islamic theology has a very large educational role in shaping the civilization of a society. However, Islamic Education today is in a dilemmatic position, between Rationalist-Critical or remaining in a position of strengthening religious theology. This article is a literature review that focuses on the theorizing of an-Nahlawi's work. By using content analysis on an-Nahlawi's main work, At-Tarbiyah bi al-Hiwar: Min Asalib at-Tarbiyah al-Islamiyah, as well as conducting a comparative analysis with another an-Nahlawi's work, Ushul at-Tarbiyah al-Islamiyah wa Asalibuha fi al-Bayt wa al-Madrasah wa al-Mujtama'. This research found several conclusions: (a) Kitab at-tarbiyah bi al-Hiwar is a study of Islamic education methods which were inspired by the educational journey undertaken by Allah to his Prophets, as well as that carried out by the Prophet Muhammad to his Companions. (b) Hiwar is an Islamic-Qur'anic terminology used in the communication of Allah to His Servant. The al-Hiwar method is the authentic method of Islam even from the beginning of the Revelation of the Qur'an. (c) The method of education with hiwar has been explained in detail in the Qur'an and the history of Islamic teaching by the Prophet Muhammad to his people, including: Hiwar Qur'ani and Nabawi, Hiwar Washfi, Hiwar Khitabi -Ta'abbudi and Hiwar at-ta 'lim. Islamic education is the transmission of knowledge and the transformation of a good soul and can provide goodness in life.